THE ACCURACY OF STUDENTS TRANSLATION OF REPORT TEXT IN THE ENGLISH LANGUAGE STUDY PROGRAM OF KHAIRUN UNIVERSITY - Rahmatia, Rahmatia; Ali, Silvani Umar; Jasin, Hamida; Adam, Samsudin Hi. (Universitas Khairun, 2023)
The purpose of this research was to find out students' translation accuracy of report text in an English education study program. This research used a descriptive qualitative method with the third-semester students as the respondents of this research. The main data source was taken from The Jakarta Post, Bicara Melalui Kain